Patients in older adult psychiatric hospital during first COVID‐19 wave. Issue 1 (6th February 2022) - Hardman, Stephen; Muthukrishnan, Sabarigirivasan; Jacobs, Benjamin; Trussell, Augusta; Chesterton, Alex
Abstract : The COVID‐19 pandemic presents unprecedented challenges to health care services across the world. When the pandemic first emerged in early 2020, health care services were forced to adapt to the new climate created by the pandemic. Here, the authors describe a case series of patients admitted to an older adult psychiatric unit when the pandemic struck, with themed discussions pertinent to the cases and an exploration of how staff adapted to this new and unfamiliar environment.